(untitled) (Birat Journal of Health Sciences, 2025)
Background: Seizure is the most common neurological medical emergency embarrassing for both parents as well as doctors. An ideal anticonvulsant should be easy-to-use, effective, and safe, and it should also have a long-lasting effect. Midazolam is a potent anticonvulsant and is rapidly absorbed from the rectal, nasal, and buccal mucosa. There are sufficient studies and data regarding efficacy of the drug in seizure control from abroad. Due to lack of availability of nasal midazolam, sufficient studies and data regarding efficacy of use of buccal midazolam in resource poor country like Nepal, we are still uncomfortable with use of buccal midazolam in acute management of convulsion. The objective of this study was to evaluate the efficacy of buccal midazolam in controlling acute seizures in children as well as neonates attending pediatric department, neonatal intensive care unit, pediatric intensive care unit and emergency of Birat Medical college Teaching Hospital. Materials and methods: It was a descriptive cross-sectional prospective study among pediatric patients and neonates. Total of 38 patient admitted with acute convulsion or developed convulsion during the hospital stay were enrolled by nonprobability consecutive sampling. Injection midazolam was used through buccal route at a dose of 0.3-0.5 mg/kg. Patients received buccal midazolam by placing the syringe between their teeth and cheek, and after drug administration the cheek was gently massaged. Patients were followed up for at least 48 hours post drug administration. Data regarding particulars of the patient, type of seizure, duration of seizure, time consumed for drug administration, time since drug administration to cessation of the seizure, any adverse effects if noticed and its management were recorded from the inpatient documents and if needed was enquired from the attending doctor and nursing staffs. Data collection tool was a pre-tested questionnaire. SPSS version 25 was used for statistical analysis of the collected data using appropriate statistical tests. Results : Among the 38 enrolled study population most of them were in the age range 1-5 years 29(76.4 %) with mean age of 2.05±0.56 years, male: female ratio of 1:1.5 and GTCS (generalized tonic- clonic convulsion) was the commonest form of seizure 32(84.21%) among the study population. The most common cause of convulsion was simple febrile convulsion with viral fever 15(39.4%). Total 36 out of 38(94.7%), had seizure controlled within 5 minutes and only 2out of 38(5.3%) had no control of seizure with buccal midazolam. The most commonly observed side effect was sedation 31/36(86.1%) among the study population. Conclusion : Buccal midazolam seemed effective in management of acute convulsion among the study population. So, we can start using buccal midazolam for acute convulsion management, it will help us to save our human resources involved in IV cannulation and will prompt our drug administration time leading to early cessation of seizures in such neurological emergency.